Employment the Object Oriented Idea with Relational Database using by Ado.Net - Ban M. (Al-Rafidain Journal of Computer Sciences and Mathematics)
With the development of technology and appearing of computers that simplified many of computer and logical applications, so the developed with all capabilities to take and give the benefit in the same time, it is necessary because the updating and extending in bank operation space by using the computer which became the spinal cord in managing these operation. This research present the system that simplicity and quicklicity of the bank job by inserting, deleting, data viewing and information and special reports extracting to any customer instead of the manual usage which is usually doing probability of mistakes is large and data corruption. We depend on ADO.NET technology to data base access which more advance technology that is presented from micro soft to support language that not special in database like visual basic, visual java, visual C++, etc. ADO.NET  technology was presented to programmers who specialist not in data base language. it enables to database access and manipulating with it in  higher degree of simple and flexible way by mixing the command s of programming language with SQL commands to use data base in all applications.